Preparation of biotinylated glyconanoparticles via a photochemical process and study of their bioconjugation to streptavidin - Narain, Ravin (Langmuir : the ACS journal of surfaces and colloids, 2007)
We report here the preparation of novel biotinylated glyconanoparticles from well-defined biotinylated glycopolymers and poly(N-isopropylacrylamide) (PNIPAAm) synthesized via the reversible addition fragmentation chain transfer (RAFT) polymerization process. The in situ reduction of the biotinylated glycopolymers, PNIPAAm, poly(ethylene glycol), and HAuCl4 via a photochemical process resulted in the formation of biotinylated gold nanoparticles. The multifunctional biotinylated glyconanoparticles were then evaluated for their bioconjugation toward streptavidin using UV-vis spectroscopy and surface plasmon resonance (SPR). The biotinylated nanoparticles underwent aggregation in the presence of streptavidin as revealed by spectrophotometry, which indicates the accessibility of the biotin for conjugation. These results were further confirmed by surface plasmon resonance even in the case of surface-immobilized streptavidin